EL PRECIO DEL PETRÓLEO Y SU INCIDENCIA EN EL CRECIMIENTO ECONÓMICO DE LOS PAÍSES PERTENECIENTES A LA ORGANIZACIÓN DE PAÍSES EXPORTADORES DE PETRÓLEO-OPEP, PERÍODO 1983-2016 - Ordóñez Tandazo, Marilin del Cisne (2018)
The petroleum has an economic importance not only because this constitute the major supply of energy, but also because it is the driver of the economic growth in countries. The main issue is the price volatility in the world market, which affects the economic growing in exporting countries by considering that their main income derives from this activity. In this context, the current research dissertation entitled “The oil price and its impact on the economic growth of member countries of the Organization of the Petroleum Exporting Countries ˗ OPEC, during the period from 1983 to 2016”. The main objective of the herewith paper was to study the oil price impact in the economic growth of the OPEC member countries, from 1983 to 2016 by using an econometric study to analyze the dynamic in a short- and long-term between variables. It was used the bibliographic, statistical, and econometrical methodology, as well as a vector autoregression (VAR) model and a vector error correction (VEC) model for the data panel. The results show that the crude oil price positively affects the GDP of the OPEC member countries with an elasticity of 3.39%, the GDP variables and the oil prices are nature I (1), and those are included in the long- and short-term. In other words, they move together through time. Hence, improving the economic structure focusing on other production alternatives unlike hydrocarbons is one of the required choices to be taken by the OPEC member countries. This should be done in other to decrease the strong dependency to this resource and to achieve a sustainable economic growing in short- and long term. Therefore, to improve the economic structure and to mainly focus on other alternative production such as the service industry, it is recommended to lessen the strong dependency in petroleum, and then to achieve a sustainable economic growth in a short- and long-term.